Does Openness Imply Greater Exposure? - Calderón, César; Loayza, Norman; Schmidt-Hebbel, Klaus (World Bank, Washington, DC, 2012)
External exposure can be measured by the sensitivity of first and second moments of economic growth to openness and foreign shocks. This paper provides an empirical evaluation of external exposure using panel data methods for a worldwide sample of countries. Controlling for domestic conditions, the paper examines the growth and volatility effects of outcome measures of trade and financial integration, as well as four types of foreign shocks: terms of trade changes, trading partners' growth rates, international real interest rate changes, and net regional capital inflows. The paper analyzes the possibility of nonlinearities by allowing the growth and volatility effects of openness to vary with the general level of economic development and by letting the effects of foreign shocks depend on the degree of trade and financial integration. The findings point toward strong non-monotonic effects of openness and external shocks on growth and volatility. Moreover, all in all, the results contradict the view that international integration increases external vulnerability by hurting growth and increasing volatility or by amplifying the adverse effect of external shocks.